DESENTRALISASI FISKAL DAN MANAJEMEN ANGGARAN DAERAH: STUDI DI JAWA TIMUR - Khusaini, Moh. (Journal of Indonesian Applied Economics, 2007)
Indonesia  has  implemented  a  new  era  of  fiscal  decentralization  and  regionalautonomy since  January 2001. One  important aspect of  fiscal decentralization  isgood  governance,  public  budgeting management,  and  decentralization  ofgovernment functions in lower level leads to achieve efficiency in allocating publicgoods despite differences in preferences of regions. This research aims at analyzingthe influence of fiscal decentralization on public budgeting management especiallycase  of District  and City  in  East  Java  Province.  There  is  an  argument  thatdecentralization  can  improve  the  quality  of  governance  and  public  services  bybringing government closer to people. By using descriptive analysis and literaturereview indicated that fiscal decentralization in Indonesia was not fully consistent inexplaining theory of fiscal decentralization. The impact of fiscal decentralization topublic budgeting management indicated that there was greater nominal change onlocal budget. However, the allocation of public budget for basic services were verylow and still far from transparency, accountability, and efficiency. This findings alsoindicated that local budget were not really public oriented yet.Keywords: fiscal decentralization, good governance, public budgeting  management